Design considerations for a three dimensional fiber optic laser Doppler velocimeter for turbomachinery applications - James, Stephen W.; Tatam, Ralph P.; Elder, R. L. (American Institute of Physics (AIP), 1997)
Single headed three dimensional (3D) laser Doppler velocimetry (LDV) geometries generally rely upon the use of three Doppler difference channels, inclined at differing angles with respect to the mechanical axes of the probe. The transformation between the nonorthogonal measurement coordinate system and the Cartesian system can result in large errors in the calculated velocities. A theoretical analysis of the geometrically induced uncertainties in measurements produced by four single headed 3D LDV configurations is presented. These considerations have lead to the development of a single headed fiber optic 3D LDV probe based on the use of two Doppler difference channels to directly measure the transverse velocity components, and a reference beam channel to measure the on axis velocity component. The f/4 probe head has a working distance of 200 mm, designed to operate within the constraints of the limited optical access available in turbomachinery applications.